Optimalisasi Taman Kota Palangkaraya sebagai Destinasi Wisata Berkelanjutan Berbasis Perda No. 14/2019 dan UU No. 18/2025 - Feby Keren Dwi Putri; Keysha Destriana; Daniel Daniel (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
Green Open Space (RTH) is a critical component of sustainable urban development, maintaining environmental balance, air quality, social interaction, and economic activities, as affirmed by Palangkaraya Regional Regulation No. 14/2019 and Law No. 18/2025, which mandate at least 20% RTH with sustainable management focused on local vegetation preservation. Public park Pasok Kameloh in Palangkaraya City exemplifies urban RTH with potential as a sustainable tourism destination; previously vibrant with significant economic activity (daily income >Rp1,000,000), it has seen a sharp decline to Rp100,000/day following roundabout construction that altered access and traffic patterns. Interviews with informants confirm adequate infrastructure including trees, ornamental plants, and spatial layout but suboptimal maintenance, such as mossy mini-ponds breeding mosquitoes and odorous deer enclosures, diminishes visitor comfort and recreational appeal. Observations reveal discrepancies between regulatory mandates and field realities, where ecological, social, and economic functions remain underutilized. Thus, in-depth studies are needed to assess management alignment and formulate optimization strategies for Taman Pasok Kameloh as a balanced tourism destination.